Hubungan umur dan pekerjaan ibu menyusui dengan pemberian ASI eksklusif - Rolita Efriani; Dhesi Ari Astuti (Universitas Muhammadiyah Semarang, 2020)
One of the efforts of the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) to reduce the Infant Morbidity and Mortality Rate (IMR) is to recommend that babies should only be breastfed for the first six months of life (exclusive breastfeeding). The coverage of exclusive breastfeeding in the Special Region of Yogyakarta was 73.3%. The lowest was in the city of Yogyakarta at 59.52%. This achievement had not yet reached the government's target of 80%. Puskesmas Umbulharjo 1 is the health center with the lowest exclusive breastfeeding coverage in Yogyakarta City at 39.15%. This study aims to determine the relationship between mothers' age and occupation with exclusive breastfeeding at Puskesmas Umbulharjo 1 Yogyakarta City. This research is an analytic survey with a cross-sectional approach. A sample of 64 mothers was taken from a population of 179 mothers who had babies aged 6-12 months. Data were analyzed by using the Chi-Square test. The results of the analysis of maternal age with exclusive breastfeeding obtained a p-value of 0.007 (p <0.05), while the analysis of maternal age with exclusive breastfeeding showed a p-value of 0.000 (p <0.05). In conclusion, there is a relationship between the mother's age and occupation and exclusive breastfeeding in the working area of Puskesmas Umbulharjo 1 Yogyakarta City